Optimalisasi Pembelajaran PAI Berbasis Kearifan Lokal Menyatukan Tradisi dan Agama dalam Kurikulum Sekolah (Prosiding Keislaman dan Sains, 2025)
Problems in optimizing Islamic Religious Education (PAI) learning based on local wisdom, which aims to unite tradition and religion, include various aspects that need serious attention, both in terms of curriculum, teaching methodology, and community acceptance. This study examines the optimization of Islamic Religious Education (PAI) learning based on local wisdom, which aims to unite tradition and religion in the school curriculum. PAI learning that integrates local wisdom not only enriches religious understanding, but also strengthens the relationship between Islamic teachings and local culture that has become part of the community's identity. In this study, it is discussed how the PAI curriculum can be adjusted to local values that exist around students, as well as the challenges and benefits of implementing this approach in the context of education in Indonesia. The method used in the study is Literature Review. The results of the study show that PAI learning based on local wisdom can increase the relevance of religious education, strengthen cultural identity, and foster a sense of tolerance and intercultural understanding.
Keywords: Optimization of PAI Learning; Local Wisdom Unites Tradition; School Curriculum